The Impact of Renewable Energy Consumption on Unemployment in Developed Countries - Omarova, Aizhan; Abubakirova, Aktolkin; Saimagambetova, Gaukhar; Amaniyazova, Gulimai; Yerkulova, Gulmira (International Journal of Energy Economics and Policy, 2025)
The utilization of renewable energy resources has been increasing in alignment with sustainable development goals, generating significant effects on economic indicators. In this context, examining the impact of renewable energy consumption on unemployment is of considerable importance for both economic policymakers and academic researchers. The primary objective of this study is to determine whether renewable energy consumption has a reducing effect on the unemployment rate. While investments in the renewable energy sector are generally believed to enhance employment, the direction and magnitude of this relationship may vary across countries. Therefore, this study investigates the relationship between renewable energy consumption and unemployment in a sample of developed countries. To conduct the analysis, fixed effects and random effects models were applied using a panel data set. The findings indicate that renewable energy consumption contributes to a reduction in the unemployment rate. Additionally, GDP and trade openness, included in the model as control variables, exhibit statistically significant negative effects on unemployment. However, the effect of inflation on the unemployment rate is found to be insignificant. The results of this study are expected to contribute to a deeper understanding of the impact of renewable energy policies on employment. Furthermore, these findings provide valuable insights for assessing the role of energy policies in economic growth and labor market dynamics.